Biopolymer composites as triboelectric layers for the development of triboelectric nanogenerator (TENG) - Delgado De Lucio, Virgilio Brian (2023)
The escalating global energy demand, propelled by rapid industrial expansion, has underscored the imperative of transitioning to cleaner and more sustainable energy sources to combat pollution and mitigate the adverse effects of global warming. Triboelectric nanogenerators (TENGs) have emerged as a promising technology capable of harnessing ambient mechanical energy and converting it into electrical power. This research initiative seeks to advance the field by focusing on the development of composite materials derived from a synergy of biopolymers extracted from natural sources, particularly potatoes, and inorganic fillers. The comprehensive objectives of this study encompass the extraction of biopolymers from natural resources, the meticulous characterization of composite materials to ascertain their mechanical, physicochemical, and morphological properties, the fabrication of TENGs employing these composite materials, and an exhaustive evaluation of the TENGs' performance metrics. Remarkably, the composite materials exhibit outstanding dielectric properties, characterized by exceptional dielectric permittivity (ε) values. At a fundamental level, these materials showcase impressive dielectric constant (ε') values, with specific examples reaching into the millions at a frequency of 1 Hz. Furthermore, the dielectric loss (ε'') values, representing the imaginary component of permittivity, also exhibit notable characteristics. For instance, certain composite materials demonstrate ε'' values that mirror the remarkable ε' values, signifying their potential to excel in energy storage applications. What sets this research apart is not only the development of materials with exceptional dielectric properties but also the exploration of their practical application in triboelectric nanogenerators. The TENGs fashioned from these composite materials consistently exhibit remarkable voltage outputs, further underscoring their potential for various energy harvesting applications.